'Cradle to grave' financial literacy programs and money management - D. Sundarasen, Sheela Devi; Rahman, Muhammad Sabbir; Rajangam, Nakiran; Sellappan, Rathakrishnan (Canadian Center of Science and Education, 2014)
The objective of this paper is to develop an integrated conceptual model, termed as the “cradle to grave model” that forms the link between the roles of educational agents, socialisation agents and the media with financial literacy and its eventual impact on money management. The paper also proposes the moderating effects of money attitude between financial literacy and money management for future empirical research. The researchers deliberated on a rigorous literature to conceptualise the model. It is envisioned that the paper will assist individual citizens and the policy makers in understanding the use of educational institutions, society and media to intellectualize financial literacy in achieving money management. The proposed conceptual model by the researchers should not be generalized until further empirical testing. Auxiliary research is desired to empirically validate the concept through systematic investigations and devising of appropriate tools for quantification. The idea is original and makes the foundational contribution for an inaugural stream of financial literacy and money management research.